Diet, Gastric Microbiota, and Metabolites in Gastric Tumorigenesis - Lanping Jiang; Harry Cheuk-Hay Lau; Ruijie Zeng; Jun Yu (Research)
Gastric cancer (GC) is one of the most common cancers worldwide particularly in Asian populations, and certain diets have been associated with increased risk of GC. Recent advances in microbial profiling technology have facilitated investigations on microbes residing on the gastric mucosa and increasing evidence has revealed the critical roles of non-Helicobacter pylori gastric microbes in gastric tumorigenesis. On the other hand, diets can affect microbial communities, causing compositional and functional shift of the microbiota. In this review, we summarize the influence of various diets including processed meat, salt-preserved food, high-fat diet, and alcohol on the development and progression of GC. We also explore microbial metabolites and host–microbe interactions in gastric tumorigenesis, alongside dietary interventions targeting the microbiota for the prevention and management against GC.